Effect of Carthamus tinctorius L. (Safflower) on National Institute of Health Stroke Scale Scores of Ischemic Stroke Patients: A Pilot Clinical Trial - Mahdi Yousefi; Payam Sasannezhad; Hassan Rakhshande; Hassan Doosti; Azadeh Saki; Zahra Baghestani Kouzegar; Hamideh Ahmadi; Elahe Delshad (Tehran University of Medical Sciences, 2022)
Experiencing complications within the first two weeks after stroke leads to a high risk of mortality and length of hospitalization. The present pilot study was intended to investigate the hypothesis that adult patients treated with safflower or not would present with fewer neurological complications following 15 days. In a randomized controlled trial, subjects diagnosed with ischemic cerebrovascular accident (CVA) based on focal neurological findings on brain imaging who met the inclusion criteria of our study were recruited from Ghaem Hospital, Mashhad, Iran, between 2016 and 2017. Thirty-six patients were included in the survey and randomly allocated into treatment (A) and control (B) groups. An oral syrup of safflower extract and nasal drop of safflower oil were additionally prescribed for group A. Group B only received a standard anti-ischemic regimen. The primary outcome measure was the National Institutes of Health Stroke Scale score (NIHSS) over 15 days. Safflower treatment led to a notably higher mean difference in the NIHSS score between the baseline score and 15-day post-treatment score in group A in comparison to group B (p < 0.001). However, adjustment for covariates (age, gender, and baseline measures) showed no significant reduction in neurological status between them (p = 0.340). There was a statistically significant difference in neurological symptom scores between the groups (p = 0.044). Based on this pilot study, adjuvant treatment with safflower in addition to the standard anti-ischemic regimen can be more effective than individual conventional drugs for treating ischemic CVA among adults.